Allergen exposure, atopy and smoking as determinants of allergy to rats in a cohort of laboratory employees. - Cullinan, P; Cook, A; Gordon, S; Nieuwenhuijsen, M; Tee, R; Venables, K; McDonald, J; Taylor, A (1999)
This study aimed to examine the relationship between exposure to rat urinary allergens, atopic status, smoking and the development of allergic symptoms and specific sensitization. It is a case-referent analysis of a cohort of 342 newly employed laboratory animal workers. Cases comprised persons developing symptoms of laboratory animal allergy or a positive skin prick test to rat urinary allergens; each was matched with up to two asymptomatic referents. Subjects were assigned to categories of exposure based on measurements of airborne rat urinary allergens. Of the cases, 80% reported that their symptoms started within 2 yrs of employment. The odds ratio (OR) for development of each symptom type (respiratory, eye or nose and skin) and of an immediate skin test reaction was increased in those with direct contact with rats. A gradient of increasing OR for the development of any such symptom across exposure categories was found; for respiratory symptoms and skin test reactions the OR for subjects in the highest exposure category were lower than those in intermediate categories, a pattern attenuated when the analysis was confined to outcomes developing within 2 yrs of first exposure. Atopy increased the OR of most outcomes as did cigarette smoking, although there was no evidence of a relationship between smoking and the development of a specific skin test reaction. In conclusion, allergen exposure was confirmed as the most important determinant of laboratory animal allergy; by implication, measures to reduce exposure may be the most effective means to reduce its incidence.